PD-1 blockade attenuates surgery-mediated immunosuppression and boosts Th1 immunity perioperatively in oesophagogastric junctional adenocarcinoma - Davern, Maria; Gaughan, Caoimhe; O’ Connell, Fiona; Moran, Brendan; Mylod, Eimear; Sheppard, Andrew D.; Ramjit, Sinead; Yun-Tong Kung, Jasmine; Phelan, James J.; Davey, Matthew G.; Ryan, Eanna J.; Butler, Christine; et al. (Frontiers in Immunology, 2023)
Introduction: This timely study assesses the immunosuppressive effects of surgery on cytotoxic Th1-like immunity and investigates if immune checkpoint blockade (ICB) can boost Th1-like immunity in the perioperative window in upper gastrointestinal cancer (UGI) patients. Methods: PBMCs were isolated from 11 UGI patients undergoing tumour resection on post-operative days (POD) 0, 1, 7 and 42 and expanded ex vivo using anti-CD3/28 and IL-2 for 5 days in the absence/presence of nivolumab or ipilimumab. T cells were subsequently immunophenotyped via flow cytometry to determine the frequency of T helper (Th)1-like, Th1/17-like, Th17-like and regulatory T cell (Tregs) subsets and their immune checkpoint expression profile. Lymphocyte secretions were also assessed via multiplex ELISA (IFN-γ, granzyme B, IL-17 and IL-10). The 48h cytotoxic ability of vehicle-, nivolumab- and ipilimumab-expanded PBMCs isolated on POD 0, 1, 7 and 42 against radiosensitive and radioresistant oesophageal adenocarcinoma tumour cells (OE33 P and OE33 R) was also examined using a cell counting kit-8 (CCK-8) assay to determine if surgery affected the killing ability of lymphocytes and whether the use of ICB could enhance cytotoxicity. Results: Th1-like immunity was suppressed in expanded PBMCs in the immediate post-operative setting. The frequency of expanded circulating Th1-like cells was significantly decreased post-operatively accompanied by a decrease in IFN-γ production and a concomitant increase in the frequency of expanded regulatory T cells with an increase in circulating levels of IL-10. Interestingly, PD-L1 and CTLA-4 immune checkpoint proteins were also upregulated on expanded Th1-like cells post-operatively. Additionally, the cytotoxic ability of expanded lymphocytes against oesophageal adenocarcinoma tumour cells was abrogated post-surgery. Of note, the addition of nivolumab or ipilimumab attenuated the surgery-mediated suppression of lymphocyte cytotoxicity, demonstrated by a significant increase in tumour cell killing and an increase in the frequency of Th1-like cells and Th1 cytokine production. Conclusion: These findings support the hypothesis of a surgery-mediated suppression in Th1-like cytotoxic immunity and highlights a rationale for the use of ICB within the perioperative setting to abrogate tumour-promoting effects of surgery and ameliorate the risk of recurrence.